2012
DOI: 10.1016/j.homp.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic effect of homeopathic preparation of Pulsatilla nigricans in Swiss albino mice

Abstract: The study showed an anxiolytic effect of homeopathic preparation of Pulsatilla nigricans comparable to that found with a standard drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…from the floor was used to observe anxiolytic behavior in animals. Another study conducted on 24 mice showed an anxiolytic effect of a homeopathic preparation of Pulsatilla nigricans comparable to that found with a standard drug (Diazepam) [29]. Mother tincture of Turnera aphrodisiaca, a remedy traditionally used for anxiety neurosis, is found to have anxiolytic activity [30].…”
Section: Resultsmentioning
confidence: 70%
“…from the floor was used to observe anxiolytic behavior in animals. Another study conducted on 24 mice showed an anxiolytic effect of a homeopathic preparation of Pulsatilla nigricans comparable to that found with a standard drug (Diazepam) [29]. Mother tincture of Turnera aphrodisiaca, a remedy traditionally used for anxiety neurosis, is found to have anxiolytic activity [30].…”
Section: Resultsmentioning
confidence: 70%
“…A previous study conducted by researchers showed an anxiolytic effect of homeopathic preparation of Pulsatilla nigricans 3X on animal model comparable to that found with a psychotropic standard [33]. Similarly, Argentum nitricum 30cH a homeopathic drug was found to possess a potent anxiolytic activity in two species rats and mice in comparison with the standard drug escitalopram, and it is suggested that high dilutions of Argentum nitricum should be administered because of its potential to produce toxic effects [34].…”
Section: Discussionmentioning
confidence: 91%
“…Changes in lifestyle and diet are an increasingly used approach for treating anxiety disorders [5]. Recent studies in experimental animals have shown that some homeopathic remedies have an anxiolytic effect comparable to conventional pharmacological treatments [6][7][8].…”
Section: Discussionmentioning
confidence: 99%